American College of Rheumatology Guidance for COVID‐19 Vaccination in Patients With Rheumatic and Musculoskeletal Diseases: Version 5. Issue 1 (8th November 2022) - Curtis, Jeffrey R.; Johnson, Sindhu R.; Anthony, Donald D.; Arasaratnam, Reuben J.; Baden, Lindsey R.; Bass, Anne R.; Calabrese, Cassandra; Gravallese, Ellen M.; Harpaz, Rafael; Kroger, Andrew; Sadun, Rebecca E.; Turner, Amy S.; et al.
Abstract : Objective: To provide guidance to rheumatology providers on the use of COVID‐19 vaccines for patients with rheumatic and musculoskeletal diseases (RMDs). Methods: A task force was assembled that included 9 rheumatologists/immunologists, 2 infectious diseases specialists, and 2 public health physicians. After agreeing on scoping questions, an evidence report was created that summarized the published literature and publicly available data regarding COVID‐19 vaccine efficacy and safety, as well as literature for other vaccines in RMD patients. Task force members rated their agreement with draft consensus statements on a 9‐point numerical scoring system, using a modified Delphi process and the RAND/University of California Los Angeles Appropriateness Method, with refinement and iteration over 2 sessions. Consensus was determined based on the distribution of ratings. Results: Despite a paucity of direct evidence, statements were developed by the task force and agreed upon with consensus to provide guidance for use of the COVID‐19 vaccines, including supplemental/booster dosing, in RMD patients and to offer recommendations regarding the use and timing of immunomodulatory therapies around the time of vaccination. Conclusion: These guidance statements are intended to provide direction to rheumatology health care providers on how to best use COVID‐19 vaccines and to facilitate implementation of vaccination strategies for RMD patients.